Nurturing Social Skills in Adolescents: Patterns of Development in Lembaga Kesejahteraan Sosial Anak (LKSA) Muhammadiyah Kota Bandung - Hassa Yanura Khairina; Yoyoh Jubaedah; Nenden Rani Rinekasari (UIN Sunan Kalijaga Yogyakarta, 2023)
Enhancing social skills in adolescents facing complex challenges, such as those residing in orphanages, follows a distinct trajectory compared to their counterparts living with families. This research endeavors to uncover the nuanced patterns of adolescent social skill development within the Muhammadiyah Child Welfare Institution (LKSA) in Bandung City. Employing a qualitative methodology with an intervention theory approach in casework, this study seeks to identify strategies for improving social skills. The results indicate that the enhancement of social skills among adolescents in LKSA Muhammadiyah Bandung City is achieved by addressing aspects of peer relations, self-management, and compliance. This is facilitated through increased adolescent participation, the cultivation of emotional intelligence, and the promotion of productive self-management. These interventions contribute to heightened self-identity and independence in social activities among adolescents. The cultivation of self-reliance becomes integral to improving adolescents' societal functioning, leading to an augmentation in social community acceptance. This positive transformation stems from bolstering the mental and physical readiness of adolescents through affective and psychomotor strengthening. Keywords: Caregiver, Social Skills, Early Adolescents Peningkatan keterampilan sosial pada remaja yang memiliki kompleksitas problem, seperti remaja yang berada di panti asuhan memiliki pola berbeda dengan remaja yang hidup bersama keluarganya. Penelitian ini bertujuan untuk mengidentifikasi pola peningkatan keterampilan sosial remaja di Lembaga Kesejateraan Anak (LKSA) Muhammadiyah di Kota Bandung. Penelitian ini menggunakan metode kualitatif dengan pendekatan teori intervensi dalam casework. Hasil penelitian menunjukkan bahwa peningkatan kemampuan sosial pada remaja di LKSA Muhammadiyah Kota Bandung dicapai dengan peningkatan pada aspek peer relation skills, self-management skill, and compliance skill melalui peningkatan partisipasi remaja, pembangunan intelegensi emosional, dan pengelolaan diri secara produktif. Tiga aspek yang dilakukan mengarah pada peningkatan identitas diri dan kemandiran remaja dalam aktivitas sosialnya. Penanaman terhadap kemandirian diri merupakan bagian dari peningkatan keberfungsian remaja dalam masyarakat agar aspek penerimaan komunitas sosialnya semakin meningkat. Peningkatan tersebut dihasilkan dari penanaman kesiapan mental dan fisik remaja melalui penguatan afektif dan psikomotorik. Kata Kunci: Pengasuh, Keterampilan Sosial, Remaja Awal